2019
DOI: 10.4103/ijo.ijo_711_18
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective study on outcomes of terminal chop technique of nuclear fragmentation in phacoemulsification and combined surgery: An observational study

Abstract: Purpose: Terminal chop, a new technique of nuclear segmentation, has been recently described in literature. The technique is considered to be a safe and effective option. Methods: We did a retrospective study to evaluate the outcome of terminal chop. Patients operated for terminal chop (phacoemulsification with or without trabeculectomy) from October 2016 to July 2018 were included in the study. Results: In all, 933 patients were included in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The CDE in our study was found to be proportional to the grade of cataract in the terminal chop technique, which was also seen by Morya et al . [ 20 ] Park et al . [ 7 ] showed that CDE in NS IV cataracts was low in the phaco-chop technique with statistical significance but only for NS IV cataracts.…”
Section: Discussionmentioning
confidence: 99%
“…The CDE in our study was found to be proportional to the grade of cataract in the terminal chop technique, which was also seen by Morya et al . [ 20 ] Park et al . [ 7 ] showed that CDE in NS IV cataracts was low in the phaco-chop technique with statistical significance but only for NS IV cataracts.…”
Section: Discussionmentioning
confidence: 99%
“…Cataract developed in this manner is known as a senile cataract [1]. The only possible cataract treatment is a surgical one, and that procedure is entitled phacoemulsification [1,2]. Cataract surgery is one of the most commonly performed surgical procedures worldwide [3].…”
Section: The Effect Of Intraocular Lens Materials and Postoperative Thmentioning
confidence: 99%
“…Phacoemulsification breaks down the blood-aqueous barrier and releases inflammatory cytokines. This local inflammatory reaction activates "E" cells that proliferate, migrate, and lead to PCO [1,2]. Many methods are used to reduce inflammation and cells migration.…”
Section: The Effect Of Intraocular Lens Materials and Postoperative Thmentioning
confidence: 99%